Decision Analysis: Point-of-care Chlamydia Testing vs. Laboratory-based Methods - Swain, Geoffrey R. (Marshfield Clinic Research Foundation, 2004)
OBJECTIVE: To evaluate and compare the performance of several different methods available for detection of Chlamydia trachomatis (Ct) infection, and to explore possible testing and treatment strategies incorporating point-of-care testing versus laboratory-based tests. DESIGN: Prospective trial and decision analysis. SETTING: Large, urban, publicly funded sexually transmitted disease clinic. PARTICIPANTS: 1,384 female patients. METHODS: Each subject was tested for Ct infection by direct fluorescent antibody (DFA, Sanofi/Kallestad, Chaska, MN), optical immunoassay (OIA, Thermo Electron, Point of Care and Rapid Diagnostics, Louisville CO), McCoy cell culture (in-house method), and polymerase chain reaction (microwell PCR, microwell assay, Roche, Branchburg NJ). RESULTS: Performing a rapid in-clinic test on women who did not meet empiric treatment criteria would have increased the overall proportion of infected persons receiving same-day treatment from 48.6% to 79.1% using DFA or 78.4% using OIA. CONCLUSIONS: Use of empiric treatment criteria and same-day point-of-care testing for patients not meeting the empiric treatment threshold appears to be an appropriate, useful, and cost-effective strategy for increasing same-day treatment of Ct infections in this population.